Can a wage subsidy system help reduce 50 per cent youth unemployment? Evidence from South Africa - Amina Ebrahim; Jukka Pirttilä (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
The paper examines the incidence and employment impacts of the Employment Tax Incentive, a South African wage subsidy system that is targeted at the employers of low-wage youth. The paper uses a triple differences strategy and survey and administrative data, covering the universe of South African workers. The results reveal that the system has not had a positive influence on the employment rate of eligible workers. The number of jobs in the region where the subsidy is the greatest has increased, but the increase is not statistically significant, perhaps due to a low take-up rate. Earnings seem to have increased for part of the eligible group, suggesting that the incidence is partly on workers.
Keywords: H24; J23; J28; H40; O12; 330; employment; taxation; youth employment; wage subsidies